Mother tongue phonological interference in english language speech - Jami Jami, Juan Carlos (2016)
The main aim of this qualitative research was to analyze the mother tongue phonological interference in English language speech in an elementary level. In a first stage, the literature review permitted to approach the main topics for understanding if the mother tongue phonological interference could be considered a problem in the second language learners’ pronunciation. To do that, the researchers found the most difficult sounds in which learners always present problems affecting their pronunciation. In a second stage, the observation to students of the level A2 of the Language Cultural Center at Technical University of Cotopaxi was applied to identify if they presented the mother tongue phonological interference at the moment of articulating English sounds….